ILRUN, a Human Plasma Lipid GWAS Locus, Regulates Lipoprotein Metabolism in Mice - Bi, Xin (Circ Res, 2020)
RATIONALE: Single nucleotide polymorphisms (SNPs) near the ILRUN gene are genome-wide significantly associated with plasma lipid traits and coronary artery disease (CAD) but the biological basis of this association is unknown. OBJECTIVE: To investigate the role of ILRUN in plasma lipid and lipoprotein metabolism. METHODS AND RESULTS: ILRUN encodes a protein that contains a ubiquitin-associated (UBA)-like domain, suggesting that it may interact with ubiquitinylated proteins. We generated mice globally deficient for Ilrun (IlrunKO) and found they had significantly lower plasma cholesterol levels resulting from reduced liver lipoprotein production. Liver transcriptome analysis uncovered altered transcription of genes downstream of lipid-related transcription factors, particularly PPARα, and livers from IlrunKO mice had increased PPARα protein. Human ILRUN was shown to bind to ubiquitinylated proteins including PPARα, and the UBA-like domain of ILRUN was found to be required for its interaction with PPARα. CONCLUSIONS: These findings establish ILRUN as a novel regulator of lipid metabolism that promotes hepatic lipoprotein production. Our results also provide functional evidence that ILRUN may be the casual gene underlying the observed genetic associations with plasma lipids at 6p21 in human.